How are you getting that x(x - 1) = x^2 - x is equal to x^2 - 1?3 - 4/(1+x) = 8/(x^2-1)
3 + 4/(x-1) = 8/(x(x-1)) - simplify
Im not asking about -1(1-x) equaling to -x+1. Im asking about x(x-1) equaling to x^2-1.im reversing the order of the denominator by using -1.
-1(1-x) = x-1
I hadnt see the prob with the 1st denom. doing the minus through reverses a subtraction but it doesnt turn addition into subtraction so -(1+x) cant be (-1+x). Besides you dont need to do anything to reverse addition; just reverse it because order doesnt mnatter in adding.3 - 4/(1+x) = 8/(x^2-1)
3 + 4/(x-1) = 8/((x=1)(x-1)) - simplify
I get the same thing. Why do you think the other ans are rite? If x=-1 then youre dividing by 0.That gives me x = 5/3 or x = -3. Not what it should work out to, which is x = 7/3 or x = -1. Why is it that I'm getting the same numbers with different signs ??
But x=-1 cant be rite bc it makes division by 0. If the book says its "the answer" then the book is wrong. Try the other ans:I think it's right because that is what my text book gives the answers as.